Redefining Roles : The Professional, Faculty, and Graduate Consultant's Guide to Writing Centers - Cheatle, Joseph; Jewell, Megan Swihart (Book collections on Project MUSE., 2020)
"Recognizes and provides sustained focus on the presence of professional, faculty, and graduate student consultants in writing centers. A number of writing centers employ non-peer consultants, yet most training manuals are geared toward undergraduate tutoring practices. This addresses this gap in the literature while initiating new conversations"--